STUDI KASUS TENTANG SERTIFIKAT GANDA DI DESA YEH SUMBUL, KECAMATAN MENDOYO, KABUPATEN JEMBRANA - Irawan, Hadi; Rai Djaja, Ida Bagus; A. Martana, Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
In publication of certificate needed by a process entangling applicant side, al adjacent land owner, Pamong Countryside and also related/relevant institution side to obtain;get letters and clarification as rights pallet related to application of certificate. " Clarification of oral goodness and also written from related parties have opportunity to the happening of forgery, daluwarsa even sometimes not true or fictious so that arise defect certificate of law." Rising Cause factors of double certificate / overlapping by Office Land of Jembrana, caused by gift of new rights by Office Land of Sub-Province of Jembrana through management of land registry systematicly discovered by the existence of collision that is careful ketidak and ketidak its in checking and checking physical datas and data of yuridis either through direct in field and also in the case of investigation of land;ground history and assessment of[is truth of ownership evidence appliance or domination of land;ground through checking of epistle exist in Office Land of Sub-Province of Jembrana. Consideration of Justice judge law Arrange the Effort State in finishing double certificate dispute (this overlapping) have as according to regulation of applicable law that is pursuant to rule of agrarian law.
Keywords: overlapping, dispute, land registry.